2019
DOI: 10.1055/a-0848-8373
|View full text |Cite
|
Sign up to set email alerts
|

Digital cholangioscopy-guided laser versus mechanical lithotripsy for large bile duct stone removal after failed papillary large-balloon dilation: a randomized study

Abstract: Background Endoscopic papillary large-balloon dilation (EPLBD) allows for the complete removal of large common bile duct (CBD) stones without fragmentation; however, a significant proportion of very large stones and stones floating above a tapering CBD require lithotripsy. Mechanical lithotripsy and cholangioscopy-guided laser lithotripsy are both effective for stone fragmentation. This study aimed to directly compare, for the first time, the efficacy of these two techniques in terms of stone clearance rate, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
1
30
0
3
Order By: Relevance
“…[11][12][13][14][15][16] ERCP with standard stone removal technique is the simplest procedure in endoscopy that most of the hospital can perform, whereas laser lithotripsy is available only in some tertiary centers especially in a low-or middle-income country. [17][18][19] It would be beneficial to the treatment planning if the success or failure of ERCP with the standard stone removal can be predicted, and a patient with a higher risk of OC conversion can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] ERCP with standard stone removal technique is the simplest procedure in endoscopy that most of the hospital can perform, whereas laser lithotripsy is available only in some tertiary centers especially in a low-or middle-income country. [17][18][19] It would be beneficial to the treatment planning if the success or failure of ERCP with the standard stone removal can be predicted, and a patient with a higher risk of OC conversion can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study investigated all kinds of cholangioscopy-guided lithotripsy, including SOC-guided lithotripsy. Recent studies focusing on SOC-guided lithotripsy reported seemingly better efficacy (Table 3) [19,26,27,[29][30][31][32][33][34].…”
Section: (3) Efficacy Of Soc-guided Lithotripsymentioning
confidence: 99%
“…Another randomized controlled trial by Angsuwatcharakon et al [33] compared SOC-guided LL and ML after a failed EPLBD. The complete stone removal rates in a single session were 100% and 63% with comparable adverse events (6% and 13%) in the SOC-guided LL and ML groups, respectively.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…9 There are two recent RCTs comparing POCS-assisted lithotripsy and the standard technique. 29,30 Buxbaum et al 29 compared POCS-assisted lithotripsy and the conventional technique including ML and EPLBD for BDS >1 cm. Complete stone removal rates were 93% in POCS-assisted lithotripsy and 67% in the conventional treatment without significant differences in the rates of adverse events (9.5% and 11.1%).…”
Section: Cholangioscopy-assisted Lithotripsymentioning
confidence: 99%
“…However, the procedure time was significantly longer in POCS-assisted lithotripsy group (120.7 and 81.2 minutes). Another RCT by Angsuwatcharakon et al 30 compared POCS-guided laser lithotripsy and ML after failed EPLBD. Complete stone removal rates in a single session were 100% and 63% with comparable adverse events (6% and 13%) in the POCS group and the ML group.…”
Section: Cholangioscopy-assisted Lithotripsymentioning
confidence: 99%